2022
DOI: 10.3389/fpsyg.2021.799456
|View full text |Cite
|
Sign up to set email alerts
|

Tutor’s Role in WhatsApp Learning Groups: A Quali-Quantitative Methodological Approach

Abstract: In recent years, digital tools, such as WhatsApp, have been increasingly deployed to support group interaction and collaboration in higher education contexts. To understand contemporary, digitally-mediated collaborative dynamics – including the role played by tutors and the situated nature of group development – robust and innovative methodologies are needed. In this paper, we illustrate how integrating qualitative methods with quantitative tools used in qualitative ways makes it possible to trace how tutors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…Meanwhile,the integration of social media in teaching speaking skills offers novel insights into student engagement and pedagogical practices (John & Yunus, 2021). Thanks to their ability to improve learning outcomes, encourage active study, and break down social barriers between teachers and students, digital technologies such as WhatsApp provide much-needed flexibility in the classroom (Annese et al, 2022). Moreover, learning outcomes, motivation, and engagement can all be enhanced by the use of technology tools into formative assessment (Kaya-Capocci et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile,the integration of social media in teaching speaking skills offers novel insights into student engagement and pedagogical practices (John & Yunus, 2021). Thanks to their ability to improve learning outcomes, encourage active study, and break down social barriers between teachers and students, digital technologies such as WhatsApp provide much-needed flexibility in the classroom (Annese et al, 2022). Moreover, learning outcomes, motivation, and engagement can all be enhanced by the use of technology tools into formative assessment (Kaya-Capocci et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…While this was a fresh move, it also raised concerns about talents, attitudes, and the ability to modify technical infrastructure. Accordingly, a setting of constant assistance and progressive development was needed (Annese et al, 2022;Naamati-Schneider & Alt, 2023).Furthermore, it has been determined that the flipped learning methodology significantly enhances speaking abilities, offering a fresh viewpoint on technology-enabled education (Santhanasamy & Yunus, 2022). Technology may be utilized in higher education to encourage critical thinking and raise student interest.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the combined e-learning and e-consultation webinars have been shown to DOI: 10.1159/000527984 not only improve knowledge and understanding of pathophysiology but also to promote clinical management by direct interaction between tutor and participant. The role of the tutor in the classroom setting and of the e-moderator in webinar teaching should not be underestimated and warrants training in digital and educational competence, assessment of educational skills as well as specific (academic) accreditation [18,[27][28][29]. However, it should be stressed that the ESPE e-Learning website is different from LMS in how it serves both students and tutors.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate for the lack of interaction in tutorials, some lecturers at the physics department formed WhatsApp groups for tutor(s) and students. WhatsApp has been found to create a virtual closeness between the tutor and the students (Annese et al, 2022;Pérez-Jorge et al, 2020). In the study by Pérez-Jorge et al (2020) students reported that WhatsApp tutorials were more effective than face-to-face tutoring, email tutoring, and google hangouts tutoring.…”
Section: Role Of Tutors In Higher Educationmentioning
confidence: 97%